Design and implementation of large scale network - F. Mohsin, Hassan; Q. Abdulmunem, Mustafa; A. Kadhim, Karrar (International Journal of Engineering and Technology, 2019)
The paper talks about designing and implementation of large scale wireless network in Engineering Campus. The main goals of this work is designing a network which able to bring sharing information, remote desktop, secured network and mobility to all network users in the coverage area of the network. Coverage range testing had been carried out at the university building. Since the result of old network is not so satisfying, a new design based on the characteristic of mikrotik, the access points and the building structure was done. This design can be applied in hotels, companies, restaurants, airports, and university departments. Â Â